Assessment and Comparison of the Visual Survey Method for Estimating Acorn Production in Holm Oak (Quercus ilex ssp. ballota) Open Woodland of Southwestern Spain - Carevic, Felipe S.; Alejano, Reyes; FERNÁNDEZ, MANUEL; Martín, Daniel (Arid Land Research and Management, 2014)
We assessed the accuracy of a visual survey method for quantification of acorn production in Holm oak in two plots located in the Huelva province of southwestern Spain during three acorn dissemination periods from 2007 to 2010. At the end of September during each period, visual surveys were used to estimate acorn numbers. Four seed traps were placed beneath the crowns of the same trees at the north, south, east, and west positions to determine acorn weight and number on a fortnightly basis during the mast seeding period (October to January). The accuracy of the visual survey was assessed by linear regression and correlation analysis. The results indicated a significant positive correlation of the two methods during all the three time periods. The resulting regression equations allowed estimation of acorn production based on visual surveys. These results suggest that the visual survey method is a simple and precise method that can be used to predict acorn production in Holm oak landscapes.
Keywords: acorn production; mediterranean landscape; visual surveys

Spatiotemporal variation in acorn production and damage in a Spanish holm oak (Quercus ilex) dehesa - Perez Izquierdo, L; Pulido, F (Forest Systems; Vol 22, No 1 (2013), 2013)
Aim of study. There is a lack of knowledge about spatio-temporal patterns of acorn production in dehesas, especially regarding the influence of different agents causing acorn damage. We examined the spatial and temporal variability on acorn production and damage in four stands within a dehesa farm in 1997, 1998 and 1999. Area of study. The study was carried out in a 1800 ha dehesa farm of Cáceres province, western Spain. Material and Methods. Acorns were sampled by means of seed traps placed in the canopy of six holm oak trees per stand. Acorn collected in it were counted and assessed for damage by Curculio weevils, Cydia moths and the bacterial pathogen Brenneria quercina . Main results. Mean acorn production for the whole study period was 44.60 acorns m -2 , which did not vary significantly either among stands or among years. The variability among individual trees was very high (0-300 acorns m -2 ). The rate of infestation by Curculio was 7.64 ± 10.72 %, by Cydia was 1.76 ± 3.33 %, whereas 10.29 ± 16.12 % of acorns were infested by Brenneria . We found no significant spatial differences, but the rates of acorn loss by insects varied among years. These rates were independent of annual acorn production and there was no correlation among damages by different pests, except between Curculio and Cydia in two crop years. Research highlights. It can be concluded that acorn crops are synchronized at the within-farm level and that the temporal variation in acorn damages can be independent of crop size. Keywords: Acorn production; Brenneria; Curculio; Cydia; dehesa; Quercus ilex; spatio-temporal variation.
Keywords: acorn production; Brenneria; Curculio; Cydia; Dehesa; Quercus ilex; spatio-temporal variation

A model to account for variations in production in southern Spain - García-mozo, Herminia; Dominguez-vilches, Eugenio; Galán, Carmen (Annals of Agricultural and Environmental Medicine, 2012)
One of the characteristics of holm-oak acorn production is its high variability among individuals and years. To examine the main causes of this fact, a study was conducted from 1998-2010 in a natural area of holm-oak in southern Spain, where floral phenology, fruit production, fruit size, airborne pollen emission and meteorology factors were analyzed with the ultimate aim of developing a model for forecasting holm-oak yield. Pollen emission during flowering season was the main factor determining the final acorn harvest, but also some meteorological variables played an important role in explaining acorn crop variations, especially humidity and temperature during the months of April and September. The reliability of the proposed model was externally validated using data not included in its construction; validation yielded acceptable results, with a minimum error of estimation. Our results appear to be very useful for planning cropping and pig feeding strategies. Further research could extend the use of airborne pollen counts in forest studies relating to anemophilous species, in order to optimize agricultural policies.
Keywords: acorn production; Aerobiology; Holm oak; model; oak forest; Phenology; pollen; quercus ilex subsp. ballota

Do ecological and silvicultural factors influence acorn mass in Holm Oak (southwestern Spain)? - Alejano, R.; Vázquez-Piqué, J.; Carevic, F.; Fernández, M. (Agroforestry Systems, 2011)
The effect of orientation, location, year, and pruning treatment on mean acorn mass in two open woodland experimental locations (Huelva, South-Western Spain) of Holm Oak (Quercus ilex L. subsp. ballota [Desf.] Samp.) was analyzed during 2001–2006. Data were analyzed by using a mixed linear model, where the covariates were tree size parameters (circumference at 80 cm height, crown size), topographic position (wet index and ﬂow length), intraspeciﬁc competition, total acorn crops per tree (weight and number), and climatic parameters. Average estimated acorn mass was 3.17 g acorn -1 in the Calan˜as location and 4.12 g acorn -1 in the San Bartolome´ location, with signiﬁcant differences between locations, among individual trees and across years. Acorns from the south sides of trees were signiﬁcantly heavier than those at other positions. The effect of pruning treatment and the interactions location 9 treatment and treatment 9 year were not signiﬁcant. Our study provides no evidence that pruning affects acorn mass. None of the analyzed covariates related to tree size, topographic position and intraspeciﬁc competition explained the difference among trees, suggesting that heritable factors play an important role. Speciﬁc climatic parameters during September, the most important month for acorn growth, may explain the effects of year and location 9 year on acorn mass. In addition, there appeared to be a ‘‘trade-off’’ between acorn mass and number of acorns.
Keywords: acorn production; Dehesa; Quercus ilex

Increased drought reduces acorn production in Quercus ilex coppices: thinning mitigates this effect but only in the short term - Sánchez-Humanes, Belén; Espelta, Josep Maria (Forestry, 2011)
In order to explore the effects of climate change on Mediterranean regenerating forests, we experimentally assessed the effects of increased drought on the reproductive attributes of Quercus ilex over a 4-year period (2005–2008). We also investigated whether traditional thinning (selection of one to a few stems per stump) could mitigate the consequences of increased drought in oak coppices. Increased drought reduced the number of reproductive trees, mean number of female flowers produced and acorn crop size, although most of these effects appeared only in the last 2 years of the experiment. In a different way, thinning enhanced all reproductive attributes, but its main effects were transient and covered only 1 or 2 years after the application of the treatments. Our results indicate that a moderate reduction in rainfall (15 per cent) reduces the reproductive ability of Q. ilex. This may have long-term negative consequences for recruitment as well as for the fauna feeding on acorns. Although traditional thinning may mitigate the consequences of increased drought, it has a remarkably short-term effect. This highlights the need to re-examine traditional forestry practices as potential adaptive strategies for coping with climate change in Mediterranean regenerating forests.
10.1093/forestry/cpq04510.1093/forestry/cpq045
Keywords: acorn production; Drought; Mediterranean forest (voyant); Quercus ilex; thinning

Plant water relations and edaphoclimatic conditions affecting acorn production in a holm oak (Quercus ilex L. ssp. ballota) open woodland - Carevic, F S; Fernández, M; Alejano, R; Vázquez-Piqué, J; TAPIAS, R; Corral, E; Domingo, J (Agroforestry Systems, 2009)
Acorn production patterns and the annual evolution of water relations parameters of Quercus ilex ssp. ballota (Desf.) Samp. in a dehesa (an open woodland forest) subject to various soil treatments (ploughing, ploughing? sowing, control) were studied in southwest Spain from June 2006 to December 2008. The effects of soil water holding capacity and effective soil depth on soil and plant water status and acorn production were also investigated. Water parameters showed signiÞcant differences between the ploughing treatment and the control, and there were also signiÞcant temporal differences. Xylem water potential ranged from- 3.4 ± 0.1 to - 0.7 ± 0.2 MPa, and cuticular transpiration was 62.4Ð 192.9 mmol H2O kg - 1 s - 1 . Acorn production did not differ signiÞcantly according to soil treatment, and showed large intra-speciÞc variability. Individual values ranged from 0 to 1,220 g m - 2 (fresh weight). Positive relationships were found between xylem water potential, cuticular transpiration and relative water content measured at midsummer, and acorn production during the three studied years. These results suggest that climatic conditions and soil water availability have a strong inßuence on plant water status, and therefore on acorn development during summer. The results also reßect the ability of this species to adapt to the Mediterranean climate by preserving water during dry periods, which to a large extent can be attributed to stomatal closure at high relative water content levels, an
Keywords: acorn production; cuticular transpiration; land use; pressure-volume curves; soil treatments; water potential

Plant water relations and edaphoclimatic conditions affecting acorn production in a holm oak (Quercus ilex L. ssp. ballota) open woodland - Carevic, F. S.; Fernández, M.; Alejano, R.; Vázquez-Piqué, J.; Tapias, R.; Corral, E.; Domingo, J. (Agroforestry Systems, 2009)
Acorn production patterns and the annual evolution of water relations parameters of Quercus ilex ssp. ballota (Desf.) Samp. in a dehesa (an open woodland forest) subject to various soil treatments (ploughing, ploughing? sowing, control) were studied in southwest Spain from June 2006 to December 2008. The effects of soil water holding capacity and effective soil depth on soil and plant water status and acorn production were also investigated. Water parameters showed signiÞcant differences between the ploughing treatment and the control, and there were also signiÞcant temporal differences. Xylem water potential ranged from- 3.4 ± 0.1 to - 0.7 ± 0.2 MPa, and cuticular transpiration was 62.4Ð 192.9 mmol H2O kg - 1 s - 1 . Acorn production did not differ signiÞcantly according to soil treatment, and showed large intra-speciÞc variability. Individual values ranged from 0 to 1,220 g m - 2 (fresh weight). Positive relationships were found between xylem water potential, cuticular transpiration and relative water content measured at midsummer, and acorn production during the three studied years. These results suggest that climatic conditions and soil water availability have a strong inßuence on plant water status, and therefore on acorn development during summer. The results also reßect the ability of this species to adapt to the Mediterranean climate by preserving water during dry periods, which to a large extent can be attributed to stomatal closure at high relative water content levels, an
Keywords: acorn production; cuticular transpiration; land use; pressure-volume curves; soil treatments; water potential

Influence of pruning and the climatic conditions on acorn production in holm oak (Quercus ilex L.) dehesas in SW Spain - Alejano, R.; Tapias, R.; Fernández, M.; Torres, Enrique; Alaejos, Joaquín; Domingo, Juan (Annals of Forest Science, 2008)
Acorn production by Quercus ilex L. ssp. ballota (Desf.) Samp. in SW Spain was assessed, and variations between years and the inﬂuence of pruning on it were examined. To this end, an experimental study was conducted at two diﬀerent sites (Calañas and San Bartolomé, in the province of Huelva) where trees were subjected to traditional (light, moderate or heavy) pruning and also to a new (crown-regeneration) pruning method. Acorn yield was quantiﬁed over a period of 5 years in the Calañas plot and 4 in the San Bartolomé plot, and found to average at 95.61 ± 0.76 g DM/m2 , which is equivalent to 6.5 ± 0.05 kg DM/tree; however, yield ﬁgures varied markedly between years depending on the particular climatic conditions. The average acorn production was correlated with the water potential in mid summer (end of July); the annual, spring and autumn rainfall; and the actual evapotranspiration for the period from September (previous year) to August. No signiﬁcant diﬀerences in acorn production between traditional pruning intensities were detected; in fact, there were only hints that heavy pruning might result in decreased acorn yields. The new pruning method used, crown-regeneration, seems promising with a view to increasing acorn yield; however, it should be tested on larger sample sizes before any ﬁnal conclusions can be drawn in this respect. Based on the results, the present health status of holm oaks in southwestern Spain (a result of sustained decline) and the low value of ﬁrewood – which used to be a very important source of income from pruning a few decades ago –, the authors recommend reducing the frequency and intensity of pruning in the dehesas of the study area.
Keywords: acorn production; Holm oak; Masting; pruning

Influence of pruning and the climatic conditions on acorn production in holm oak (Quercus ilex L.) dehesas in SW Spain - Alejano, R; TAPIAS, R; Fernández, M; Torres, Enrique; Alaejos, Joaquín; Domingo, Juan (Annals of Forest Science, 2008)
Acorn production by Quercus ilex L. ssp. ballota (Desf.) Samp. in SW Spain was assessed, and variations between years and the inﬂuence of pruning on it were examined. To this end, an experimental study was conducted at two diﬀerent sites (Calañas and San Bartolomé, in the province of Huelva) where trees were subjected to traditional (light, moderate or heavy) pruning and also to a new (crown-regeneration) pruning method. Acorn yield was quantiﬁed over a period of 5 years in the Calañas plot and 4 in the San Bartolomé plot, and found to average at 95.61 ± 0.76 g DM/m2 , which is equivalent to 6.5 ± 0.05 kg DM/tree; however, yield ﬁgures varied markedly between years depending on the particular climatic conditions. The average acorn production was correlated with the water potential in mid summer (end of July); the annual, spring and autumn rainfall; and the actual evapotranspiration for the period from September (previous year) to August. No signiﬁcant diﬀerences in acorn production between traditional pruning intensities were detected; in fact, there were only hints that heavy pruning might result in decreased acorn yields. The new pruning method used, crown-regeneration, seems promising with a view to increasing acorn yield; however, it should be tested on larger sample sizes before any ﬁnal conclusions can be drawn in this respect. Based on the results, the present health status of holm oaks in southwestern Spain (a result of sustained decline) and the low value of ﬁrewood – which used to be a very important source of income from pruning a few decades ago –, the authors recommend reducing the frequency and intensity of pruning in the dehesas of the study area.
Keywords: acorn production; Holm oak; Masting; pruning

Life-history traits in an evergreen Mediterranean oak respond differentially to previous experimental environments - Benayas, J. M. R.; Cuesta, Bárbara; Villar-Salvador, P.; Jáuregui, Pedro (Web Ecology, 2008)
Living organisms respond both to current and previous environments, which can have important consequences on population dynamics. However, there is little experimental evidence based on long-term field studies of the effects of previous environments on the performance of individuals. We tested the hypothesis that trees that establish under different environmental conditions perform differently under similar post-establishment conditions. We used the slow-growing, evergreen Mediterranean oak Quercus ilex subsp. rotundifolia as target species. We analyzed the effects of previous environments, competition effects and tradeoffs among life-history traits (survival, growth, and reproduction). We enhanced seedling establishment for three years by reducing abiotic environmental harshness by means of summer irrigation and artificial shading in 12 experimental plots, while four plots remained as controls. Then these treatments were interrupted for ten years. Seedlings under ameliorated environmental conditions survived and grew faster during early establishment. During the post-management period, previous treatments 1) did not have any effect on survival, 2) experienced a slower above-ground growth, 3) decreased root biomass as indicated from reflectivity of Ground Penetration Radar, 4) increased acorn production mostly through a greater canopy volume and 5) increased acorn production effort. The trees exhibited a combination of effects related to acclimation for coping with abiotic stress and effects of intra-specific competition. In accordance with our hypothesis, tree performance overall depended on previous environmental conditions, and the response was different for different life-history traits. We recommend early management because it increased plot cover, shortened the time to attain sexual maturity and increased the amount of acorn production. Plots such as those assessed in this study may act as sources of propagules in deforested agricultural landscapes thus aiding natural establishment of new plants
Keywords: acorn production; canopy volume; competition; environmental conditions; Growth; management (voyant); shoot/root ratio

Life-history traits in an evergreen Mediterranean oak respond differentially to previous experimental environments - Benayas, J M R; Cuesta, Bárbara; VILLAR-SALVADOR, P; Jáuregui, Pedro (Web Ecology, 2008)
Living organisms respond both to current and previous environments, which can have important consequences on population dynamics. However, there is little experimental evidence based on long-term field studies of the effects of previous environments on the performance of individuals. We tested the hypothesis that trees that establish under different environmental conditions perform differently under similar post-establishment conditions. We used the slow-growing, evergreen Mediterranean oak Quercus ilex subsp. rotundifolia as target species. We analyzed the effects of previous environments, competition effects and tradeoffs among life-history traits (survival, growth, and reproduction). We enhanced seedling establishment for three years by reducing abiotic environmental harshness by means of summer irrigation and artificial shading in 12 experimental plots, while four plots remained as controls. Then these treatments were interrupted for ten years. Seedlings under ameliorated environmental conditions survived and grew faster during early establishment. During the post-management period, previous treatments 1) did not have any effect on survival, 2) experienced a slower above-ground growth, 3) decreased root biomass as indicated from reflectivity of Ground Penetration Radar, 4) increased acorn production mostly through a greater canopy volume and 5) increased acorn production effort. The trees exhibited a combination of effects related to acclimation for coping with abiotic stress and effects of intra-specific competition. In accordance with our hypothesis, tree performance overall depended on previous environmental conditions, and the response was different for different life-history traits. We recommend early management because it increased plot cover, shortened the time to attain sexual maturity and increased the amount of acorn production. Plots such as those assessed in this study may act as sources of propagules in deforested agricultural landscapes thus aiding natural establishment of new plants
Keywords: acorn production; canopy volume; competition; environmental conditions; Growth; management (voyant); shoot/root ratio

Driving competitive and facilitative interactions in oak dehesas through management practices - Moreno Marcos, G; Obrador, J J; García, E; Cubera, E; Montero, M J; Pulido, F; Dupraz, C (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.
Keywords: acorn production; forage yield; light; microclimate; root system; soil resources

Driving competitive and facilitative interactions in oak dehesas through management practices - Moreno Marcos, G.; Obrador, J. J.; García, E.; Cubera, E.; Montero, M. J.; Pulido, F.; Dupraz, C. (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.
Keywords: acorn production; forage yield; light; microclimate; root system; soil resources